Potensi madu pada peningkatan jumlah sel spermatogenik tikus (rattus norvegicus) yang kekurangan nutrisi - Listyorini, Linda; Hernawati, Tatik; suprayogi, tri wahyu (Ovozoa: Journal of Animal Reproduction, 2021)
This study aimed to determine honey's potential in increasing the number of spermatogenic cells (spermatogonium, spermatocyte and spermatid) of rats (Rattus norvegicus) with nutritional deficiencies. Twenty four male rats (Rattus norvegicus) were randomly divided into four groups. Negative control (K-) mice was not fasted nor given honey. Positive control (K+) mice was fasted for 5 days without the administration of honey. The treatment group rats were fasted for 5 days followed by administration of honey 30% (P1) and 50% (P2) in drinking water for 10 days. On the 76th day all rats were sacrificed and their testes were collected for histological slides using Hematoxylin-Eosin staining. The results showed that fasting treatment for five days (group K +) caused a decrease (p <0.05) in the number of spermatogonia cells, spermatocytes and spermatids compared to those of the normal mice (group K–). Administration of 50% honey (group P2) for 10 days caused an increase (p <0.05) in the number of spermatogonia cells, spermatocytes and spermatids compared to the K + group mice. In P2 group, the number of spermatogonia cells was lower (p <0.05), while the number of spermatocytes and spermatids was not significantly different than in the K– group mice. It could be concluded that the administration of honey was able to regenerate the testicular tissue of rats with nutritional deficiency by increasing the number of spermatogenic cells in the seminiferous tubules.